Phenotypic and Molecular Screening of Long Grain Rice (Oryza sativa L.) Genotypes Against Leaf Blast Disease - Gudepu, S.; Katragadda, S.; Chennamadhavuni, D. R. (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during rabi (December, 2021 to March, 2022) at Agricultural Research Station (ARS), Kampasagar, Nalgonda district, Telangana, India to identify long grain rice genotypes comprising of released varieties and advanced breeding lines (ABLs) with blast resistance, superior yield, and good grain quality using Marker-Assisted Selection (MAS). Rice blast disease caused by Magnaporthe oryzae causes significant economic losses worldwide. Genetic resistance in cultivars was the most-effective strategy to manage this disease, offering an alternative to chemical control. Leaf blast resistance screening revealed that 5 and 14 genotypes were found resistant and moderately resistant to blast. Molecular profiling with 11 polymorphic markers linked to blast resistance genes (Pi1, Pi9, Pi20, Pi20, Pi2, Pi54, Pib, Pib, Pitp, Pizt and Pi38) identified the highest number of positive alleles in RNR 15435 (6) followed by KPS 13054 (5) and WGL-44 (5). Majority of the rice accessions had the R-genes Pitp and Pi20 but, genes Pizt, and Pi2 were present in all 30 rice accessions and none of these had Pi9. The most promising genotypes for blast resistance were RNR 15435, KPS 13054, KPS 12349, KNM 118, KPS 12774, KPS 3272 and R-RHZ-IB-80 which demonstrated strong marker-trait associations and had multiple resistance genes Pi1, Pi2, Pi20, Pi38, Pi54, Pib, Pitp, and Pizt. The associated R-genes might be utilized in rice breeding programmes through marker-assisted breeding, and the identified resistant rice accessions could be used as prospective donors for the production of new leaf blast resistant varieties in India.